2009
DOI: 10.2337/db08-0949
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Reduces Mitochondrial Content in Skeletal Muscle and Affects Glycemic Control

Abstract: OBJECTIVE— Blockade of angiotensin (Ang) II has been shown to prevent new-onset type 2 diabetes. We focused on the effects of AngII on muscle mitochondria, especially on their biogenesis, as an underlining mechanism of type 2 diabetes. RESEARCH DESIGN AND METHODS— C2C12 cells and C57bl/6 mice were used to examine roles for AngII in the regulation of muscle mitochondria and to explore whether the effect was mediated by type 1 AngII receptor (AT1R) or type 2 receptor (AT2R). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 40 publications
4
51
4
Order By: Relevance
“…However, in a model of IR associated with excessive RAS activation, impaired State 3 mitochondrial respiration was observed in mouse skeletal muscle (Takada et al 2013). Moreover, in mouse skeletal muscles, chronic Ang II infusion caused glucose intolerance and mitochondrial abnormalities together with increased mitochondrial ROS generation (Mitsuishi et al 2009). …”
Section: Mechanisms Of H 2 O 2 Generationmentioning
confidence: 99%
“…However, in a model of IR associated with excessive RAS activation, impaired State 3 mitochondrial respiration was observed in mouse skeletal muscle (Takada et al 2013). Moreover, in mouse skeletal muscles, chronic Ang II infusion caused glucose intolerance and mitochondrial abnormalities together with increased mitochondrial ROS generation (Mitsuishi et al 2009). …”
Section: Mechanisms Of H 2 O 2 Generationmentioning
confidence: 99%
“…The major source of ROS is believed to be the mitochondrial electron transport system (13). In addition, many factors, such as ischemic renal injury (6), advanced glycation end products (5), angiotensin II (ANG II) (25,36), besides HG (14), may also induce excessive ROS production and mitochondrial dysfunction, which eventually leads to apoptosis and necrosis of the renal tubular cells (35). Our laboratory's previous studies have shown that HG can reduce the mitochondrial membrane potential (⌬m) and enhance the release of mitochondrial cytochrome c (mCyt.C) into the cytosol with activation of caspases and ultimately apoptosis in tubular cells (32).…”
mentioning
confidence: 99%
“…24 Another explanation would be an increase in fatty acid release from visceral adipose tissue. When compared to WT mice, the AT2R-KO mice did not display any change in glucose tolerance, circulating NEFA and triglycerides levels, in accordance with the known relative resistance of mice vs. rats to diet-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 99%